2011
DOI: 10.1111/j.1365-2842.2011.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital image processing versus visual assessment of chewed two‐colour wax in mixing ability tests

Abstract: Two-colour chewing gum and wax have been widely used as test foods to evaluate the ability to mix and knead a food bolus. The mixing of the colours has been assessed by computer analysis or by visual inspection. Reports contradict each other about whether computer analysis and visual assessment could equally well discriminate between the masticatory performances of groups of participants with different dental status. This study compares the results of computer analysis of digital images of chewed two-colour wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 14 publications
4
42
0
1
Order By: Relevance
“…; van der Bilt et al. ) who reported more muscle activity with harder than softer foods and concluded that the muscle activity depends on the texture of the food. Both reduced tactile function (as a result of the absence of periodontal ligament receptors) and loss of inhibitory reflexes cause an impaired control of the maximum biting force with hard food which is well reflected in the high muscle activity (Karkazis ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; van der Bilt et al. ) who reported more muscle activity with harder than softer foods and concluded that the muscle activity depends on the texture of the food. Both reduced tactile function (as a result of the absence of periodontal ligament receptors) and loss of inhibitory reflexes cause an impaired control of the maximum biting force with hard food which is well reflected in the high muscle activity (Karkazis ).…”
Section: Discussionmentioning
confidence: 98%
“…; van der Bilt et al. ; Toman et al. ) and may be attributed to the presence of implant attachments that stabilize the denture, reduce the pain, and allow the patients to exert higher bite forces during function (Fontijn‐Tekamp et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bilt et al . demonstrated that the unequal distribution of chewed two‐colour wax could be evaluated accurately and easily after flattening the bolus. Schimmel et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Van der Bilt et al. ). The MAI has no unit of effect and ranges from 5 to 30 (respectively, fully mixed tablet and pristine tablet).…”
Section: Methodsmentioning
confidence: 98%